True gardens of the gods : Californian-Australian environmental reform, 1860-1930 - Tyrrell, Ian R. (Berkeley, Calif. : University of California Press, 1999)
One of the most critical environmental challenges facing both Californians and Australians in the 1860s involved the aftermath of the gold rushes. Settlers on both continents faced the disruptive impacts of mining, grazing, and agriculture; in response to these challenges, environmental reformers attempted to remake the natural environment into an idealized garden landscape. As this cutting-edge history shows, an important result of this nineteenth-century effort to "renovate" nature was a far-reaching exchange of ideas between the United States - especially in California - and Australia. Ian Tyrrell demonstrates how Californians and Australians shared plants, insects, personnel, technology, and dreams, creating a system of environmental exchange that transcended national and natural boundaries. True Gardens of the Gods traces a new nineteenth-century environmental sensibility that emerged from the collision of European expansion with these frontier environments
Introduction: True Gardens of the Gods -- 1. Renovating Nature: Marsh, Mueller, and Acclimatization -- 2. Wheat, Fruit, and Henry George: The Political Economy of California Horticulture -- 3. Trees in the Garden: The Australian Invasion -- 4. The Remarkable Pines of Monterey: Californian Softwoods in Australasia -- 5. Irrigation and the Garden in California: Popular Thought -- 6. Dreams and Ditches: Deakin, Australian Irrigation, and the Californian Model -- 7. Transplanting Garden Landscapes: The Chaffey Ventures and Their Aftermath -- 8. To Australia and Back: Elwood Mead and the Vision of Closer Settlement -- 9. Bug versus Bug: California's Struggle for Biological Control -- 10. Blasting the Cactus: Biological Control in Australia -- Epilogue: The Death of the Garden?
Includes bibliographical references (pages 291-299) and index.
Print version record.
English.
JSTOR
Keywords: Plant introduction -- California -- History; Plant introduction -- Australia -- History; Agriculture -- California -- History; Agriculture -- Australia -- History; Human ecology -- California -- History; Human ecology -- Australia -- History; California -- Relations -- History; Australia -- Relations -- History; Pest introduction -- California -- History; Pest introduction -- Australia -- History; California -- Relations; Australia -- Relations; Plantes -- Introduction -- Californie -- Histoire; Plantes -- Introduction -- Australie -- Histoire; Agriculture -- Californie -- Histoire; Agriculture -- Australie -- Histoire; Californie -- Relations; Australie -- Relations; Animaux et plantes nuisibles -- Introduction -- Californie -- Histoire; Animaux et plantes nuisibles -- Introduction -- Australie -- Histoire; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- Crop Science; TECHNOLOGY & ENGINEERING -- Agriculture -- Agronomy -- General; NATURE / Environmental Conservation & Protection; Agriculture; Human ecology; Pest introduction; Plant introduction; International relations; Australia; California; History